Kebijakan Proteksionisme Indonesia Guna Menstabilkan Iklim Investasi Nasional dan Mengkapitalisasi Kondisi Perang Dagang Amerika Serikat – Tiongkok - Saifulloh, Moh. Roziq (Jurnal Hukum Lex Generalis, 2020)
Trade liberalization is the elimination or reduction of restrictions or barriers to the free exchange of goods between countries. On the other hand, the Protectionism policy of the United States (U.S.) to Chinese products led to a trade war between the two countries. The impact of the U.S.-China trade war has an impact on fluctuations in the value of JCI in Indonesia, so protectionism policies are needed in accordance with national and international legal instruments to stabilize the national investment climate and capitalize on the conditions of the U.S.-China trade war. In this paper, the author uses a statutory approach, conceptual approach, and historical approach, so that this research is classified as normative juridical research or also called doctrinal law research.